Optimization of Sports Injury Treatment through the Application of Artificial Intelligence: Methods for Effective Prevention, Diagnosis and Rehabilitation - Milić, Marko Kimi; Sinanović, Šćepan; Jestrović, Vladimir (Sport - nauka i praksa, 2025)
Artificial intelligence (AI) is increasingly being applied in various medical fields, including the treatment of sports injuries. This paper focuses on analyzing the potential of AI technologies to enhance the prevention, diagnosis, and rehabilitation of sports injuries. Through a systematic review of existing studies and technological advancements, key strategies introduced by AI in this field have been identified. The research methodology includes big data analysis, image processing, machine learning, and customized algorithms for prediction and rehabilitation monitoring. Additionally, models for automated injury pattern recognition have been examined, which can significantly contribute to preventative measures and reduce injury incidence. The study results indicate substantial improvements in treatment efficiency, reduced recovery time, and increased diagnostic accuracy, directly facilitating a faster return to sporting activities. The paper concludes by emphasizing the need for further integration of AI technologies into sports medicine and the development of tailored AI solutions that address the specific needs of athletes, considering various risk factors and individual training characteristics.
Keywords: artificial intelligence; sports injuries; prevention; diagnosis; rehabilitation; machine learning; data analysis